PROFIL MEDIA E-LEARNING BERBASIS WEB PADA MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN - NARARIA WILDANI WIDYANINGTYAS (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2012)
Abstract: This research aims to 1.)Producing web based e- Learning as a learning media 2.)Knowing students response towards web based e-learning media on structure and function plant tissues.  The phases of this research are preparation phase, media creation phase, and limited try out phase to fifteen 3rd grade students of Sidoarjo 4 senior high school. The result of this research showed that the improved e-learning media is proper. This result was shown from the research of competent lecturers and biology teachers that included media format aspect quality content 100% for each aspect. The student response result toward the improved e-learning media showed an average of 87,40%. Keywords: e-learning,web, structure and function of plant tissue.